Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0022887
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Primes Human Mesenchymal Stem Cells for Enhanced Chondrogenesis

Abstract: Human mesenchymal stem cells (hMSCs) are multipotent cells capable of differentiating into a variety of mature cell types, including osteoblasts, adipocytes and chondrocytes. It has previously been shown that, when expanded in medium supplemented with fibroblast growth factor-2 (FGF-2), hMSCs show enhanced chondrogenesis (CG). Previous work concluded that the enhancement of CG could be attributed to the selection of a cell subpopulation with inherent chondrogenic potential. In this study, we show that FGF-2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 38 publications
3
74
0
Order By: Relevance
“…Many efforts have been made to study the molecular signals involved in FGF-2 induced proliferation of chondrocytes [43][44][45], with the hope of preventing the formation of fibrous cartilage tissue caused by FGF-2 treatment [ 46,47]. Our data uncover a positive role of FGF-1 in proliferation of hPCs, at least in co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 66%
“…Many efforts have been made to study the molecular signals involved in FGF-2 induced proliferation of chondrocytes [43][44][45], with the hope of preventing the formation of fibrous cartilage tissue caused by FGF-2 treatment [ 46,47]. Our data uncover a positive role of FGF-1 in proliferation of hPCs, at least in co-culture with MSCs.…”
Section: Discussionmentioning
confidence: 66%
“…[ 43,44 ] On the other hand, FGF-2 can be used to maintain hBM-MSCs in PEG gels in a nonosteogenic differentiated state. Moreover, while it has been shown that FGF-2 not only suppresses dedifferentiation of hBM-MSCs but also enhances their chondrogenic potential [45][46][47][48] in Figure 3 c that 14 d after culture in FGF-2 hBM-MSCs can still be adipogenically and osteogenically differentiated indicating the maintenance of their multipotency.…”
Section: D Msc Monocultures Can Be Osteogenically Differentiated In mentioning
confidence: 88%
“…A recent study demonstrated that FGF7 promotes preadipocyte proliferation [32]. In addition, FGF2 also induces cell growth and chondrogenic and osteoblast differentiation in bone marrow-derived mesenchymal cells [33,34]. However, the role of FGFs in adipogenic differentiation of hMSCs, especially FGF7 and FGF14, remains elusive.…”
Section: Discussionmentioning
confidence: 99%